Gene expression pattern of CCL2, CCL3, and CXCL8 in patients with bipolar disorder - Ghoryani, Mohsen (J Res Med Sci, 2019)
BACKGROUND: Bipolar disorder (BD) is one of the most important psychiatric disorders in the world. There is evidence suggesting the role of inflammatory mediators such as chemokines in the etiology of BD. The objective of the current study was to evaluate the gene expression of CCL2, CCL3, and CXCL8 in patients with BD and compare them to healthy controls. MATERIALS AND METHODS: A total of 48 patients with confirmed BD and 48 healthy controls enrolled in this study. All patients were recruited from April to August 2016 at Ibn-Sina Psychiatric Hospital, Mashhad University of Medical Sciences, Mashhad, Iran. RNA was extracted from the whole blood samples and then cDNA was synthesized. Gene expression of CCL2, CCL3, and CXCL8 was measured using SYBR(®) Green real-time polymerase chain reaction. The difference of delta-CT values between patients and healthy controls was compared with the independent samples t-tests. RESULTS: CCL2 and CXCL8 genes expressed at higher levels in patients with BD as compared to healthy controls, but not significant. On the contrary, we found lower expression levels for CCL3 gene in our patients compared to healthy controls, but the difference was not statistically significant. CONCLUSION: Our findings do not show an association between the gene expression of CCL2, CCL3 and CXCL8 and BD. Increasing the sample size and evaluation on the gene expression of other chemokines in depression and mania phases of BD might be helpful to get a better conclusion.